Pengaruh Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) Terhadap Hasil Belajar Ilmu Pengetahuan Sosial (IPS) Siswa Kelas VIII di SMP Swasta Tamansiswa Pematangsiantar Tahun Ajaran 2025/2026: Penelitian - Daniel Andre Devany Sijabat; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on student learning outcomes in Social Sciences (IPS) subjects in class VIII of Tamansiswa Private Junior High School Pematangsiantar in the 2025/2026 Academic Year. This type of research is a quantitative experiment with a Nonequivalent Control Group Design. The research sample consisted of two classes, namely the experimental class using the CIRC learning model and the control class using the lecture method. The data collection technique used learning outcome tests in the form of pretests and posttests. Data analysis was carried out through normality tests, homogeneity tests, and t-tests using the SPSS 26 application. The results showed that there was a significant increase in student learning outcomes after the implementation of the CIRC learning model. The average pretest score of the experimental class was 48.41, increasing to 72.76 in the posttest, while the control class increased from 44.55 to 68.00. Based on the results of the t-test, a significance value of 0.000 <0.05 was obtained, which means that Ha was accepted and H0 was rejected. Thus, it can be concluded that the application of the Cooperative Integrated Reading and Composition (CIRC) learning model has a significant effect on student learning outcomes in social studies subjects.